2020
DOI: 10.3390/app10238757
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Biomechanical Parameters of Human-Wheelchair Systems during Ramp Climbing with the Use of a Manual Wheelchair with Anti-Rollback Devices

Abstract: Purpose: The main purpose of the research conducted was the analysis of kinematic and biomechanical parameters measured during manual wheelchair ramp-climbing with the use of the anti-rollback system and the comparison of the values tested with the manual wheelchair climbing the same ramp but without any modifications. The paper presents a quantitative assessment relating to the qualitative research of the anti-rollback system performed by another research team. Method and materials: The article presents the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…4 Muscle activity . Most studies reported peak EMG value [ 29 , 30 , 33 , 38 , 45 , 48 , 50 , 60 ], but five studies reported mean EMG activity during propulsion [ 24 , 29 , 46 , 50 , 61 ]. Although most studies reported normalized muscle activity using maximum voluntary contraction testing, one article reported un-normalized EMG activity as voltage measured by the sensor [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Muscle activity . Most studies reported peak EMG value [ 29 , 30 , 33 , 38 , 45 , 48 , 50 , 60 ], but five studies reported mean EMG activity during propulsion [ 24 , 29 , 46 , 50 , 61 ]. Although most studies reported normalized muscle activity using maximum voluntary contraction testing, one article reported un-normalized EMG activity as voltage measured by the sensor [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it was observed that muscle activity of all of the studied muscles was found to consistently increase with the grade. Some studies reported muscle activity during locomotion higher than the one observed during maximum voluntary contraction testing for some subjects [ 46 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…The first one is an analysis of the propulsion wheel angle of rotation resulting from the trajectory of the hand's movement during the propelling phase; the second one is the mathematical formalisation of the propulsion wheel angle of rotation described as a function of the propelling phase duration. These research objectives are justified by the ongoing work on modifications and improvements to wheelchair manual propulsion systems [5,[20][21][22]. When developing such innovative manual propulsion systems, it is necessary to provide data reflecting the so-called human factor, in this particular case, referring to the course of the angle of rotation of the propulsion wheel during the propelling phase.…”
Section: Introductionmentioning
confidence: 99%
“…EMG is also a tool used for diagnosing the impact of a technical device on a patient. This application of EMG is used by engineers designing rehabilitation devices [24][25][26]. Another very interesting application of EMG is recognition of unvoiced or silent speech by observing the activity of muscles associated with speech apparatus [27].…”
Section: Introductionmentioning
confidence: 99%